Histopathological Finding of Burn Healing Using Ambarella Leaf (Spondias dulcis F.) and Coconut Oil on Rats (Rattus norvegicus) - Ummu Balqis; Rasmaidar R; Marwiyah M (Jurnal Medika Veterinaria, 2014)
The aims of this research was to find out the histopathological finding of II B degree burns healing on rats (Rattus norvegicus) usingambarella leaf (Spondias dulcis F.) and coconut oil. Experimental animals used were 12 male Wistar strain rats,with the age of 2-3 months, and100-200 grams BW. This study used 4 treatment groups, each treatment consisted of 3 rats. The II B degree burns on the backs of rats madeusing electrical solder connected to the metal. Treatment was done 2 times a day for 21 days, P1 (double distilled water), P2 (ambarella leaf anddouble distilled water), P3 (coconut oil), and P4 (ambarella leaf and coconut oil). Skin sampling was performed on day 7, 14, and 21 forhistopathological preparations and then stained with haematoxylin and eosin. Parameters observed such as inflammatory reactions anddistribution of collagen tissue was analyzed descriptively. The results showed that the P4 group contained fewer inflammatory cell infiltrationand more dense collagen tissue than group P1, P2, and P3. It can be concluded that group P4 (ambarella leaf and coconut oil) showshistopathological finding burns healing better than the other treatment groups.____________________________________________________________________________________________________________________Key words: ambarella leaf, burns, coconut oil, healing